(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In general, studying the structure and function of society helps us realize that we are part of a larger social system and that our behavior and decisions can have an impact on social well-being. By understanding the structure and function of society, we can better adapt, interact, and benefit society as a whole.